BIO PROSPECTING MARINE HALOPHYTE Salicornia brachiata FOR MEDICAL IMPORTANCE AND SALT ENCRUSTED LAND DEVELOPMENT - Oswin D Stanley (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Halophytes continue to be either under or unexplored in India. Many halophytic plants are of economicvalue and have industrial applications in the form of essential oils, medicinal, alcohol, fiber, latex, pulp,cosmetics etc. Salicornia spp extensively occur along Gujarat and Tamil Nadu coasts in the regularly(20-50 tides month-1) inundated inter tidal zones. Expanding saline wastelands, dubious rains,recurring droughts and soil erosion due to absence of green belt between sea and land ultimately leadto low productivity and poverty in these coastal regions.Seawater Agriculture is the strategy to link ecology and livelihood. Utilizing Salicornia to rehabilitatethe land and bio-prospecting biomedical compounds is a promising concept besides addressing theissues of desertification, salt intrusion and ultimately poverty alleviation. It is rational to implementpilot projects in different locations with commercial motives entangled with research conceptsstandardization.